Users’ satisfaction level towards the facilities provided at the Mass Rapid Transit (MRT) Station / Nurul Ashiqin Rosman - Nurul Ashiqin, Rosman (2019)
Nowadays, many types of public transportation have been developed to help the people to travel from one place to another place without have to trapped in traffic jam when travelling by car or personal transportation. Public transport modes such as transit buses or city buses, light rail transit (LRT), commuter rail system and mass rapid transit (MRT) have been established in many part of the world including in Malaysia. Thus, the accessibilities of a facilities at the public transportation such as Mass Rapid Transit (MRT) is necessary due to the importance of public transport to Malaysia people. The facilities are needed to satisfy the needs and necessities of a Mass Rapid Transit (MRT) users. The aim of this research to study the users’ satisfaction level towards the facilities provided at the Mass Rapid Transit (MRT). The purpose of this study is to identify the types of facilities provided at the MRT station, to determine the level of users’ satisfaction toward facilities provided at the Mass Rapid Transit (MRT) station and to suggest on improvement of facilities provided at the Mass Rapid Transit (MRT) station. The scope of this research is focusing on the facilities available at the MRT station. A total of 354 questionnaires was distributed to the respondents at the Muzium Negara MRT station. The data collected then transferred to the SPSS software to be analysed and the outcome of the analysis has been presented in the form of table and chart. The result from the survey showed that the level of satisfaction of the respondent towards the facilities in the MRT station were between moderate to high.